Business strategy and performance in Indonesia's service sector. Issue 2 (3rd May 2016) - Yuliansyah, Yuliansyah; Rammal, Hussain G.; Rose, Elizabeth
Abstract : Purpose: The relationship between strategic choices and performance in service firms in emerging markets has remained largely under-researched. This study aims to address this issue by studying the performance of financial institutions in the context of Indonesia's political, institutional and socio-cultural environment. Design/methodology/approach: Using institutional theory, the authors analyzed data collected using surveys and interviews with senior managers in Indonesian financial institutions. Findings: The authors find that the regulative and normative elements have forced organizations to incorporate the values set by the external institutional bodies. The organizations have undertaken structural isomorphism in response to culture-cognitive elements, and differentiate themselves by focusing on the provision of quality customer service and enhanced customer satisfaction. Originality/value: The authors provide new insights by studying how the political and institutional environment and choice of strategy influences performance of the services sector in emerging economies.